CAPITAL STRUCTURE AND FIRM PERFORMANCE: AN EVIDENCE OF TRANSPORTATION, LOGISTIC AND WAREHOUSE COMPANY LISTED AT IDX 2018-2022 - Ayu Shafira Rachmani; Eko Rizkianto (Sean Institute, 2023)
A company needs to invest as a form of increasing the growth of the company. The capital structure in this activity is considered very important because it relates to the company's strategy in financing their investment activities so that it shows growth in company performance. This study aims to determine the effect of capital structure on the performance of transportation, logistics, and warehousing companies listed on the Indonesia Stock Exchange from 2018 to 2022. Capital structure as an independent variable is measured based on the total debt to equity ratio (DER). The use of economic value added (EVA) and market value added (MVA) as the dependent variable to describe the firm performance. Method used in this study is panel data regression considering the characteristics of the data which are time series and cross sectional which were carried out in 21 transportation, logistics, and warehousing companies in Indonesia. The results found in this study indicate that the total debt to equity ratio affect negatively on Economic Value Added (EVA). Meanwhile, the total debt to equity ratio has no effect on Market Value Added (MVA).